TANGGUNG JAWAB KEPERDATAAN BIDAN DALAM PELAYANAN KESEHATAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In carrying out their health services obligations, midwifes need to comply with professional standards because failure to observe careful and diligent practice may be a ground for holding the midwife accountable. Injured patient reserves the right to file a lawsuit against the midwifes by invoking breach of contract or wrongful acts as the basis of liability. Therefore, in carrying out his/her profession, a midwife must comply with professional standards, standard operating procedures, and regulated code of conduct. This article will analyse matters pertinent to profession, malpractice, and their efforts to heal. Keywords: midwife, health services, civil duties.